Mejoramiento poblacional del arroz en Uruguay: caracterización y desarrollo de germoplasma - Pérez de Vida, Fernando B.; Blanco, PH; Abadie, T; Tais, M; Châtel, M.; Borrero Correa, Jaime C. (Empresa Brasileira de Pesquisa Agropecuária, 2000)
In Uruguay, the varieties required by local and external markets are developed, using traditional breeding methods, by the Rice Breeding Program of the Instituto Nacional de Investigación Agropecuaria (INIA). Although these methods have been successful, recent studies have shown a yield plateau. As a complementary strategy, a population improvement project was launched in 1996 to broaden the genetic base of Uruguayan germplasm, and to generate a much-improved source for developing lines over the medium term. Gene pool GPIRA T-10 was introduced from the Centro Internacional de Agricultura Tropical (CIAT), Colombia, in 1996. After evaluating and characterizing it, we saw a need to develop local populations with higher potential to achieve the goals of the national breeding program. In collaboration with the CIAT/CIRAD Recurrent Selection Project, we developed four new populations: PURG-1\0\0\0, PURG-2\0\0\0, PURG-3\0\0\0, and PURG-4\0\0\0. This paper discusses the strategy for developing and handling these germplasm materials.